Variabilidade genética e endogamia em um plantel comercial de codornas (Coturnix japonica) - Resende, Lucileide Vilela (2013)
This study aimed to estimate the genetic diversity and inbreeding, perform genetic relationships analysis, and estimate heritability for morphometric variables in quails using microsatellite markers. We used the following morphometric measurements: weight (PO), length (CO), and width (LO) of eggs, weight (P), body length (CC), length (CB), height (AB), and width (LB) of beak, wing length (CA), tarsus length (CT), and toe length (CD). We verified the genetic association for the morphometric variables in the progenies. Also, we checked whether features P, CC, CB, AB, LB, CA, CT, and CD were related to the amount of offspring (QF) from adults in quail families from a commercial flock. We used seven cages containing six females and two males each, which resulted in a progeny of 672 individuals. The genotypes of the individuals were obtained in an automated DNA sequencer. Genotypes were used for genetic diversity, inbreeding, and genetic link analyzes of two generations, and to perform analyzes of variance components, descriptive statistics, Pearson correlations, heritability, t-test, and Utest of Mann-Whitney. In the parental generation we found high probability of combined paternity exclusion (PE = 0.999956), low probability of combined identity (PI = 1.47 x 10-13), and that null alleles frequency was near zero. The values of expected (He) and observed (Ho) heterozygosity, and polymorphism information content (PIC) were equal to 0.768, 0.766 and 0.734, respectively, indicating a high genetic diversity. When we assessed only the progenies, the genetic diversity was maintained (He = 0.760, Ho = 0.757 and PIC = 0.725). The inbreeding coefficient (f) was low and not significant. The genetic link analysis was efficient to assign paternity and maternity for 97% of the progeny. The weight of the offspring at birth and the variables analyzed in eggs are highly correlated. There is also a significant correlation between most measures analyzed. Estimates of heritability values were considered moderate to high. The average number of offspring was 15.93 per female, and 44.6 for males. Females were, on average, heavier than males. The QF was only correlated with the CC in females. We found significant difference between the weight of heavier males when compared to lighter males, but the comparison between QF and weight category was not significant. These results indicated that the 12 microsatellite markers used in the study were robust for the genetic relationships and genetic variability analysis in this species. We also found that the egg’s variables and progeny’s weight were highly correlated, and heritability estimates ranged from moderate to high in the variables analyzed. Females were heavier than males, QF was correlated only with CC in females, and there was no significant difference between heavier males and lighter males. All these information may be useful in future breeding programs for Coturnix japonica.